2020
DOI: 10.1155/2020/2146160
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence of Periodontal Disease and Lack of Its Surveillance

Abstract: Background. Periodontal disease is a public health problem and is strongly associated with systemic diseases; however, its worldwide distribution is not fully understood. Objective. To evaluate global data of periodontal disease: (1) among adolescents, adults, and older population and (2) in low-, middle-, and high-income countries. Methods. This ecological study included data of periodontal disease from the World Health Organization’s data bank which are based on the Community Periodontal Index of Treatment N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
258
1
35

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(300 citation statements)
references
References 38 publications
6
258
1
35
Order By: Relevance
“…2 The prevalence was differed significantly in low (28.7%), lower-middle (10%), upper-middle (42.5%), and high-income countries (43.7%). 3 The prevalence was different in East Africa with a prevalence of 89.8% in Egypt, 4 63.9% in Sudan, 5 and 53.4% in Ethiopia. 6 Periodontal disease has been associated with poor lifestyle, low-socioeconomic status, poor access to health care, and health-related risk behaviors (smoking, obesity, alcohol intake, carbohydrate diets, and poor oral hygiene practice) in developing countries.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…2 The prevalence was differed significantly in low (28.7%), lower-middle (10%), upper-middle (42.5%), and high-income countries (43.7%). 3 The prevalence was different in East Africa with a prevalence of 89.8% in Egypt, 4 63.9% in Sudan, 5 and 53.4% in Ethiopia. 6 Periodontal disease has been associated with poor lifestyle, low-socioeconomic status, poor access to health care, and health-related risk behaviors (smoking, obesity, alcohol intake, carbohydrate diets, and poor oral hygiene practice) in developing countries.…”
Section: Introductionmentioning
confidence: 98%
“… 2 The prevalence was differed significantly in low (28.7%), lower-middle (10%), upper-middle (42.5%), and high-income countries (43.7%). 3 The prevalence was different in East Africa with a prevalence of 89.8% in Egypt, 4 63.9% in Sudan, 5 and 53.4% in Ethiopia. 6…”
Section: Introductionmentioning
confidence: 98%
“…A recent study on the global prevalence of periodontal disease revealed that the percentage of adults affected by various stages of periodontal disease is 100% in China, India, and Belarus. 3 In addition, over half of the adult population in Belarus (76%), Germany (73%), Nepal (64%), Poland (62%), Malaysia (60%), Libya (56%), Iran (53%), and Taiwan (53%) have periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis has a high worldwide prevalence with nearly 40% in the age group of the 35–44-year-olds and nearly 50% in the age group of the 65–74-year-olds [ 31 ]. There is increasing evidence that periodontitis can promote the development of systemic diseases such as atherosclerosis and subsequent CVD.…”
Section: Discussionmentioning
confidence: 99%